THE RELATIONSHIP BETWEEN NUTRITIONAL STATUS AND HEMOGLOBIN LEVELS WITH THE MENSTRUAL CYCLE STUDENTS AT MAN 2 SITUBONDO - Yuningsih (Fetus : Journal of Midwifery, 2023)
Menstruation is a process of removing blood, mucus, and cells from the uterine mucosa accompanied by desquamation of the endometrium that occurs regularly around 14 days after ovulation (WHO, 2018). The research objective was to determine the relationship between nutritional status and hemoglobin levels with the menstrual cycle. This type of observational analytic research with cross sectional design. The research population was students of class XII MAN 2 Situbondo, totaling 69 students with 60 sample using simple random sampling technique. The research instrument used a questionnaire and data analysis with Spearman's Rank. Analysis of the relationship between nutritional status and the menstrual cycle obtained a p-value of 0.010 < α 0.05, which means there is a relationship between nutritional status and the menstrual cycle in female students of MAN 2 Situbondo. And the results between hemoglobin levels and the menstrual cycle were p-value 0.165 > α 0.05, that mean there was no relationship between hemoglobin levels and the menstrual cycle in female students of MAN 2 Situbondo. The menstrual cycle is influenced by the age of menarche, nutritional status, anemia, physical activity and stress levels